2011
DOI: 10.1111/j.1523-5378.2011.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Real-Time PCR Stool Assay for Helicobacter pylori Detection and Clarithromycin Susceptibility Testing in Brazilian Children

Abstract: This assay proved to be appropriate for H. pylori clarithromycin susceptibility testing, particularly in children populations where a high prevalence of clarithromycin-resistant strains is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…A further step was undoubtedly represented by the detection of point mutations conferring antibiotic resistance in bacterial DNA fecal samples. Table 1 reports the main studies on antibiotic susceptibility (clarithromycin) performed on H. pylori stool DNA by RT-PCR[32-38]. For each study, diagnostic accuracy parameter and reference standard are reported.…”
Section: Noninvasive Molecular Testsmentioning
confidence: 99%
“…A further step was undoubtedly represented by the detection of point mutations conferring antibiotic resistance in bacterial DNA fecal samples. Table 1 reports the main studies on antibiotic susceptibility (clarithromycin) performed on H. pylori stool DNA by RT-PCR[32-38]. For each study, diagnostic accuracy parameter and reference standard are reported.…”
Section: Noninvasive Molecular Testsmentioning
confidence: 99%
“…Development of a detection procedure using methods such as direct sequencing may be helpful in these cases. 25,26 In a previous Japanese study, more than 90% of CAM-resistant strains of H. pylori had the A2143G mutation. 27 In this study, only one CAM-resistant strain (A2142C) was detected and a CAM resistancerelated mutation (A2143G) from fecal DNA was detected in the same patient.…”
Section: Discussionmentioning
confidence: 95%
“…Instead, in this study, we distinguished mutant‐type and wild‐type 23S rRNA sequences using software. Development of a detection procedure using methods such as direct sequencing may be helpful in these cases …”
Section: Discussionmentioning
confidence: 99%
“…Because of the high clinical importance of H. pylori infection, numerous diagnostic methods based on nucleic acid technology for its detection in clinical, biological, and environmental samples have been developed (22,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%